Caries risk assessment in school children using reduced cariogram model - Taqi, M.; Razak, I.A.; Ab-Murat, N. (Professional Medical Publications, 2017)
Objective: To estimate the percentage of children with low, moderate and high caries risk; and to determine the predictors of caries risk amongst 11-12 year old Pakistani school children. Methods: Subjects' caries risk was assessed using the Cariogram programme. The survey was done among school children in Bhakkar district of Punjab, Pakistan. Caries and plaque level were assessed using the DMFT and Sillnes and Loe indices respectively, while diet content and frequency were assessed using a three-day diet diary. Results: A total of 226 children participated in this study, giving a response rate of 75%. Most subjects (39.8%) were in the low risk category with DMFT score of 0. The overall mean DMFT score was 1.49 (+/- 0.63). Linear and multiple regressions were performed to evaluate the predictability of caries risk. Previous experience of dental caries was found to be the most relevant predictor of caries risk (40%). Conclusion: The levels of caries risk amongst Pakistani 11-12 year old school children were generally low. Past caries experience was the most significant factor in predicting future caries lesion in this sample population.